Pelatihan Penyusunan Laporan Keuangan dan Pajak Entitas yang Tidak Menyelenggarakan Sistem Akuntansi Bagi Guru SMK dan SMA Pengajar Akuntansi di Kota Pontianak - Farizi, Zulham Al; Andriana, Susan; Suherma, Linda (Jurnal Pengabdi, 2019)
This activity aims to provide a basic theory of how to compile financial statements for entities that do not hold accounting information systems, provide skills to utilize available technology to conduct financial statement preparation, and introduce the types of information technology used in tax reporting. Currently the industrial world has entered the Industrial era 4.0 graduates from education providers must have technology-based competencies in order to be able to have competitiveness and keep up with the times. Industries that are running domestically, should be able to be carried out and carried out by local workers by increasing their capacity. So that they are not just occupying low positions